2013
DOI: 10.1016/j.bbamcr.2012.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Plastid-to-nucleus communication, signals controlling the running of the plant cell

Abstract: The presence of genes encoding organellar proteins in both the nucleus and the organelle necessitates tight coordination of expression by the different genomes, and this has led to the evolution of sophisticated intracellular signaling networks. Organelle-to-nucleus signaling, or retrograde control, coordinates the expression of nuclear genes encoding organellar proteins with the metabolic and developmental state of the organelle. Complex networks of retrograde signals orchestrate major changes in nuclear gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 176 publications
0
64
0
Order By: Relevance
“…This was a significant result for the field as it defined a mechanism for plastid signaling, and is unsurprisingly included in numerous models for this pathway (e.g. Chan et al, 2016;Bobik and Burch-Smith, 2015;Terry and Smith, 2013;Barajas-López et al, 2013). Subsequent studies from the same group have suggested that PTM functions in retrograde signaling from the chloroplast to regulate flowering under high light and in the integration of light and chloroplast retrograde signaling during de-etiolation .…”
mentioning
confidence: 99%
“…This was a significant result for the field as it defined a mechanism for plastid signaling, and is unsurprisingly included in numerous models for this pathway (e.g. Chan et al, 2016;Bobik and Burch-Smith, 2015;Terry and Smith, 2013;Barajas-López et al, 2013). Subsequent studies from the same group have suggested that PTM functions in retrograde signaling from the chloroplast to regulate flowering under high light and in the integration of light and chloroplast retrograde signaling during de-etiolation .…”
mentioning
confidence: 99%
“…1) and the constitutively high values of F 0 . Retrograde signals originating in the redox imbalances generated by the alternative electron partitioning might initiate reprogramming of nuclear gene expression, especially of photosynthetic genes (PhANG) and also in extreme situations arrest the developmental program of the plastid (Barajas-Lopez et al, 2013).…”
Section: Physiological Impact Of Enhanced Cef In Psfd1 Overexpressorsmentioning
confidence: 99%
“…Several plastid signals have been reported to influence the transcription of nuclear genes encoding plastidlocalized proteins in a process termed retrograde signaling (Rodermel, 2001;Fernández and Strand, 2008;Barajas-López et al, 2013a). One of the identified retrograde signals is linked to the tetrapyrrole biosynthetic pathway, and several reports have shown that perturbations of the tetrapyrrole pathway result in major changes of nuclear gene expression (Strand et al, 2003;Ankele et al, 2007;Pontier et al, 2007;Mochizuki et al, 2008;Moulin et al, 2008;Zhang et al, 2011).…”
mentioning
confidence: 99%